Synthesis and Characterization of some Metal Complexes with (3Z ,5Z, 8Z)-2-azido-8-[azido(3Z,5Z)-2-azido-2,6bis(azidocarbonyl)-8,9-dihydro-2H-1,7-dioxa-3,4,5triazonine-9-yl]methyl]-9-[(1-azido-1-hydroxy)methyl]-2H1,7-dioxa-3,4,5-triazonine – 2,6 – dica - Taher, Thuraya A .; Mahdi, Waleed K .; Musa, Falih H . (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The reaction of LAs-Cl8 : [ (2,2- (1-(3,4-bis(carboxylicdichloromethoxy)-5-oxo-2,5dihydrofuran-2-yl)ethane â€“ 1,2-diyl)bis(2,2-dichloroacetic acid)]with sodium azide in ethanol with drops of distilled water has been investigated . The new product L-AZ :(3Z ,5Z,8Z)-2azido-8-[azido(3Z,5Z)-2-azido-2,6-bis(azidocarbonyl)-8,9-dihydro-2H-1,7-dioxa-3,4,5triazonine-9-yl]methyl]-9-[(1-azido-1-hydroxy)methyl]-2H-1,7-dioxa-3,4,5-triazonine â€“ 2,6 â€“ dicarbonylazide was isolated and characterized by elemental analysis (C.H.N) , 1H-NMR , Mass spectrum and Fourier transform infrared spectrophotometer (FT-IR) . The reaction of the L-AZ withM+n: [ ( VO(II) , Cr(III)  ,Mn(II) , Co(II) , Ni(II) , Cu(II) , Zn(II) , Cd(II) and Hg(II)] has been investigated  and was isolated and characterized by FT- IR , UV-Visible ,electrical conductivity, magnetic  susceptibilities  at 22 Co . Atomic absorption and molar ratio Spectroscopic evidence showed  that the binding of metal ions were through the azide(Î¼1,1-N3) Triazonine(3,5 â€“N3) and carboxyl moieties , resulting in a six â€“ coordinating metal ions (Cr(III),Mn(II),Co(II),Ni(II) and Cu(II) ) .The VO(II) , Zn(II) ,Cd(II), andHg(II) were coordinated through azido (Î¼-1,1-N3) , triazonine(3,5-N3) only forming square pyramidal for VO(II) and  tetrahedral geometry for Zn(II) , Cd(II) ,and Hg(II)Î², Ì for Ni(II) , Cr(III) complexes were calculated too . The molar ratio and metal estimation showed , the ratio of LAZ to metal ions was (10:1) ; (M/L) .